2010
DOI: 10.5551/jat.1560
|View full text |Cite
|
Sign up to set email alerts
|

Association of Endothelial Nitric Oxide Synthase Gene Polymor-phisms with Early-Onset Ischemic Stroke in South Indians

Abstract: Aim:The aim of this study was to investigate the association of T-786C, G894T and 4a/b polymorphisms in the endothelial nitric oxide synthase (eNOS) gene with early-onset ischemic stroke in South Indians. Methods: We enrolled 177 patients diagnosed with ischemic stroke aged between 15 to 45 years and 219 age-and gender-matched healthy controls. Genotypes of eNOS T-786C, G894T and 4a/b were identified by polymerase chain reaction and restriction fragment length polymorphism. Results: The allele and genotype fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
1
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 42 publications
(47 reference statements)
1
16
1
1
Order By: Relevance
“…Relatively small studies have shown variable associations between individual NOS3 variants and NOS3 haplotypes with the risk of stroke (Howard et al, 2005;Majumdar et al, 2010;Saidi et al, 2010;Song et al, 2010;Yemisci et al, 2009). A meta-analysis of casecontrolled studies through 2008 examining the 894G > T and 27-bp VNTR variants of NOS3 in stroke suggested that the 4a allele was not associated with an increased risk, but that the 894T allele may have a marginally increased risk of stroke (odds ratio 1.14; 95% CI 0.99,1.31; Tao and Chen, 2009).…”
mentioning
confidence: 99%
“…Relatively small studies have shown variable associations between individual NOS3 variants and NOS3 haplotypes with the risk of stroke (Howard et al, 2005;Majumdar et al, 2010;Saidi et al, 2010;Song et al, 2010;Yemisci et al, 2009). A meta-analysis of casecontrolled studies through 2008 examining the 894G > T and 27-bp VNTR variants of NOS3 in stroke suggested that the 4a allele was not associated with an increased risk, but that the 894T allele may have a marginally increased risk of stroke (odds ratio 1.14; 95% CI 0.99,1.31; Tao and Chen, 2009).…”
mentioning
confidence: 99%
“…Only two studies, to the best of our knowledge, [11,16] performed in Caucasians have reported the role of NOS3 gene variations in determining the NO levels and their association with stroke. Two studies from South Asian-Indian population have also reported the association of some NOS3 gene SNPs with ischemic stroke but the studies were not elaborate and did not involve the evaluation of NO levels [18,19]. Our present study involved a comparative assessment of NO levels and NOS3 gene SNPs detected by SSCP, in young Asian Indian stroke patients and Table 3 Allelic and genotypic associations.…”
Section: Discussionmentioning
confidence: 90%
“…These metabolite levels have been previously shown to be associated with NOS3 SNPs [11]. However, only a limited number of studies have extensively looked at the possibility of NOS3 SNPs being a risk factor for ischemic stroke in young Asian Indian population [18,19]. The present study aimed at determining the role of NO levels and genetic variations in the NOS3 promoter/exonic regions towards the development of IS in young Asian Indians.…”
Section: Introductionmentioning
confidence: 95%
“…Relevant studies identified were; five for MTHFR C677T [22]–[26], three for PDE4D SNP 83 [27][29] and 2 studies each for eNOS 4a/4b [30], [31], ACE [32], [33], ApoE E4/E4 [34], [35], FVL G1691A [36], [37], PDE4D SNP 87 and 32 [38], [39] and IL10 [40], [41] genes. Two studies each reporting different stroke sub types (Cerebral Venous Thrombosis (CVT) and arterial paediatric ischemic stroke) were found for genes MTRR G66A [42], [43], MTR A2756G [42], [43], MTHFR A1298C [42], [43] and FVL A4070G [36], [42], [43], and therefore ORs for risk were not estimable.…”
Section: Resultsmentioning
confidence: 99%